English and Croatian in the Typology of Rhythmic Systems - Josipović, Višnja (1994)
This paper discusses the place of English and Croatian in the typology of rhythmic systems. It is mainly concerned with the differences between stress-based and syllable based languages. It is shown that rhythmic distortions are based primarily on production, rather than perception. As a result of the tonal differences between the two languages the rhythmical distortions under consideration inevitably lead to intonational distortions. Special attention is paid to the implications that these differences have for the creation of the impression of foreign accent.
ENG